TITEN SCIENCE-BASED GROUP DISCUSSION MODEL (ROUND ROBIN BRAINSTORMING) AS AN EFFORT TO IMPROVE LEARNING ACHIEVEMENT IN SOCIAL SCIENCE EDUCATION - Aji Permana, Septian (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study began with initial observations conducted by previous researchers which showed that student learning outcomes were quite low, with the percentage of students reaching 43.75% with the lowest score of 45 and the highest score of 85. This study aims to determine the implementation of the Round Robin Brainstorming learning model based on TITEN science in improving student learning achievement in Social Studies subjects. This study was conducted in class VIII B of SMP Negeri 3 Gamping. The research method used was classroom action research, and data collection techniques used observation and tests as student evaluation assessment instruments. The results obtained in Social Studies Education learning are the implementation of the Round Robin Brainstorming learning model based on TITEN science with student learning outcomes in cycle I reaching a percentage of 65.63%, a maximum score of 95, and a lowest score of 40. Meanwhile, in cycle II, it increased to a percentage of 84.38%. The highest score is 100, and the lowest score is 45. The novelty in this study is the Round Robin Brainstorming Learning Model based on local wisdom owned by the community in understanding an educational value obtained from nature with Indonesian people calling it (TITEN science). The impact of this research is that the application of the Round Robin Brainstorming model based on TITEN Science can improve the learning achievement of class VIII B students at SMP Negeri 3 Gamping with a student graduation index reaching 100%.